Analisis Faktor-Faktor yang Menyebabkan Adopsi Mobile Commerce di Kota Semarang - Sutrisno, Sutrisno (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
Mobile phones were originally wireless devices for one-on-one voice communication. Mobile commerce has changed the purpose and capabilities of mobile devices. This study aims to examine the factors that enable the adoption of m-commerce in Semarang. The theories used in this research are UTAUT and SERVQUAL as well as the constructs of trust and security. A quantitative approach method based on SEM-PLS was applied. Respondents were drawn from m-commerce users across different platforms in Semarang, Indonesia, through an online questionnaire. The findings of this study found positive and significant evidence of an integrated model with consumers' behavioral intention in utilizing m-commerce. This means that researchers and practitioners can gain a more comprehensive understanding of how consumers respond to m-commerce and what influences their intention to use it. The combination of UTAUT and service quality measured by SERVQUAL can provide valuable insights into optimising consumer experience in m-commerce and increasing the adoption rate of the platform.